Alterations in platelet count and mean platelet volume as predictors of patient outcome in the respiratory intensive care unit. (21st May 2014) - Sezgi, Cengizhan; Taylan, Mahsuk; Kaya, Halide; Selimoglu Sen, Hadice; Abakay, Ozlem; Demir, Melike; Abakay, Abdurrrahman; Tanrikulu, Abdullah Cetin
Abstract Introduction Thrombocytopenia is associated with increased mortality in intensive care unit (ICU) patients. Mean platelet volume (MPV) reflects platelet function and activation. Elevated MPV is associated with poor outcomes and increased mortality rate in diseases that are commonly encountered in the respiratory ICU. Methods We retrospectively enrolled 95 patients who died in the ICU (dead group), 80 patients who improved and were transferred from the ICU (survived group), and 80 healthy individuals as controls. Laboratory parameters including erythrocyte sedimentation rate (ESR), C‐reactive protein (CRP), albumin, and complete blood count (CBC) were recorded within 24 h on admission and transfered from the ICU or died. White blood cell (WBC) count, hemoglobin (Hb), red cell distribution width, MPV, platelet distribution width (PDW), and platelet count (PC) were obtained from the CBC. Results Admission PC and MPV levels were not different in the survived and dead groups. But in the survived group, admission WBC, MPV and PDW levels decreased, while PC increased when compared with admission levels. In the dead group, admission MPV and PDW levels increased, while PC decreased with respect to admission levels. The admission mean PC of the dead group was 182 103, which was above the thrombocytopenia limit. The ratio of admission thrombocytopenia was 45.3% in the dead group, which was significantly higher than that of the survived group (13.8%) (P < 0.001) Conclusions Increasing MPV and decreasing platelet count may alert intensivists to the worse course of disease in patients who had normal platelet counts at ICU admission. The development of thrombocytopenia may also be essential to assessing the outcome of ICU patients